2021
DOI: 10.33552/ojdoh.2021.04.000588
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Prognostic Significance of Perineural Invasion in Oral Squamous Cell Carcinoma

Abstract: Objective: To measure the frequency of perineural invasion in oral squamous cell carcinoma, to correlate its presence with various variables and to assess its impact upon prognosis.Design: A retrospective analytical study was planned.Place and Duration of study: Patients were identified with oral squamous cell carcinoma who had underwent surgical excision over the past 7 years in Rehman Medical institute. The duration of the study was 6 months.Methodology: Pathology reports were collected; and based upon the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In the Versha et al's study, 40.5% of squamous cell carcinoma patients showed PNI. The findings of PNI positivity in squamous cell carcinoma in various studies are summarized in Table 1 [ 13 - 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Versha et al's study, 40.5% of squamous cell carcinoma patients showed PNI. The findings of PNI positivity in squamous cell carcinoma in various studies are summarized in Table 1 [ 13 - 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…Zubair et al [ 13 ] showed a statistically significant correlation between PNI and lymph node involvement using the chi square test. The authors found that PNI was present in 49.3% of clinically positive nodes.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations